The importance of gas infrastructure in power systems with high wind power penetrations. (1st April 2016) - Devlin, Joseph; Li, Kang; Higgins, Paraic; Foley, Aoife
Highlights: The first multi-vector gas and power system analysis for Ireland is performed. Power system security is vulnerable to outages on the gas network. Economic operation of the power system is negatively affected by gas network outages. Excessive power system reserve allocation can occur over a transmission constraint. Wind forecast error results in large utilisation swings for importing gas pipelines. Abstract: Gas fired generation currently plays an integral support role ensuring security of supply in power systems with high wind power penetrations due to its technical and economic attributes. However, the increase in variable wind power has affected the gas generation output profile and is pushing the boundaries of the design and operating envelope of gas infrastructure. This paper investigates the mutual dependence and interaction between electricity generation and gas systems through the first comprehensive joined-up, multi-vector energy system analysis for Ireland. Key findings reveal the high vulnerability of the Irish power system to outages on the Irish gas system. It has been shown that the economic operation of the power system can be severely impacted by gas infrastructure outages, resulting in an average system marginal price of up to €167/MW h from €67/MW h in the base case. It has also been shown that gas infrastructure outages pose problems for the location of power system reserve provision, with a 150% increase in provision across a power system transmission bottleneck. Wind forecast error was shown to be a significant cause for concern, resulting in large swings in gas demand requiring key gas infrastructure to operate at close to 100% capacity. These findings are thought to increase in prominence as the installation of wind capacity increases towards 2020, placing further stress on both power and gas systems to maintain security of supply.